Synthesis, Characterization, and Antibacterial Efficacy of Borosilicate Compound against Escherichia coli - Vera Barrios, Bertha Silvana (2023)
In this study, a glassy borosilicate compound was synthesized using recycled glass and natural clays. Even though glass recycling is the generally accepted standard practice for managing glass waste, fine fractions of container soda-lime glass or cullet of other compositions are still disposed of in landfills. Thus, advanced upcycled products that offer greater economic motivation for implementation in industry may be the key to success, but these are frequently linked to alternative methods of product synthesis. Here, a simple and facile route of borosilicate compound production has been synthesized and characterized. The physicochemical characterization of the compounds was carried out to determine their properties and the antibacterial efficacy of the synthesized compound against Escherichia coli (E. coli) was investigated. The structural and spectroscopic characteristics were identified as a compound that conformed to quartz, cristobalite, and silicon hexaboride (SiB6). For the antibacterial activity, two test types were typically performed; in the first one, the dilutions of the grind were combined with chloramphenicol at a concentration of 20 µg/mL to perform a synergistic action against the bacteria and in the second one, only the amorphous borosilicate compound was tested against E. coli ATCC 25922 strains. The treatments applied considered the dilutions from 8 to 40 µg/mL. The minimum inhibitory concentration (MIC) sensitivity tests began with incubation at 37 °C in the tubes and subsequent seeding in Petri dishes for colony-forming unit (CFU) counting. The results obtained indicated that the samples possessed a productive antibacterial effect, which support their use in various biomedical applications.